The Spectrum of B Cell Functions in Atherosclerotic Cardiovascular Disease - Smeets, Diede; Gisterå, Anton; Malin, Stephen G.; Tsiantoulas, Dimitrios (Frontiers in Cardiovascular Medicine, 2022)
B cells are a core element of the pathophysiology of atherosclerotic cardiovascular disease (ASCVD). Multiple experimental and epidemiological studies have revealed both protective and deleterious functions of B cells in atherosclerotic plaque formation. The spearhead property of B cells that influences the development of atherosclerosis is their unique ability to produce and secrete high amounts of antigen-specific antibodies that can act at distant sites. Exposure to an atherogenic milieu impacts B cell homeostasis, cell differentiation and antibody production. However, it is not clear whether B cell responses in atherosclerosis are instructed by atherosclerosis-specific antigens. Dissecting the full spectrum of the properties of B cells in atherosclerosis, will pave the way for the designing of innovative therapies against the devastating consequences of ASCVD.